Pharmacokinetics and tolerability of a veterinary phenobarbital product in healthy dogs - Jukier, Tom; Gross, Amanda; Boothe, Dawn (Frontiers in Veterinary Science, 2024)
Phenobarbital has been used for many decades in both human and veterinary epileptic patients. Many formulations for a particular drug exist, most of which are marketed for humans. Recently a veterinary specific phenobarbital product has been introduced to the market in the United States. Utilizing a specific formulation to treat patients may help decrease the issue of bioequivalence between one pharmaceutical product to another. Therefore, the goal of this study was to determine single and multiple dosing pharmacokinetics and tolerability of a veterinary specific phenobarbital product over a 4-week time period. 8 Healthy dogs from a canine research colony were used in the study. Overall, this phenobarbital formulation was well tolerated in the dogs in this study. Cmax, Tmax, half-life, and AUC after single 12mg/kg oral dose were 23.5µg/mL, 4.2 hours, 94 hours, and 2758 h*µg/mL. Following chronic dosing, these parameters were 29.1 µg/mL, 3.4 hours, 70 hours, and 2971 h*µg/mL respectively. This formulation demonstrated a mean absolute bioavailability of 100%, with similar pharmacokinetic properties to previously published data.